Fusobacterium nucleatum Aggravates the Progression of Colitis by Regulating M1 Macrophage Polarization via AKT2 Pathway - Liu, Le; Liang, Liping; Liang, Huifen; Wang, Mingming; Lu, Bingyun; Xue, Meng; Deng, Jun; Chen, Ye (Frontiers in Immunology, 2019)
Disordered intestinal flora and discordant immune response are associated with the development of ulcerative colitis (UC). Recent work has described the ability of macrophages to undergo repolarization towards a proinflammatory M1 or anti-inflammatory M2 phenotype in response to particular bacterium-derived signals. Fusobacterium nucleatum (F.nucleatum) is a species of intestinal commensal bacteria with potential pathogenicity, but its association with UC and how it may contribute to progression of UC is largely unknown. In this study, we provide new evidence that F.nucleatum accumulated heavily in the intestine of UC patients, and accompanied by the secretion of IFN-γ and the skewing of M1 macrophages. Mechanistically, our data showed that F.nucleatum aggravated dextran sodium sulfate (DSS)-induced colitis in the production of Th1-related cytokines IFN-γ through AKT2 signaling pathway in vitro and in vivo. To further confirm the disease-relevance of these shifts in macrophage repolarization in response to F.nucleatum, stimulated bone marrow derived macrophages (BMDMs) were transferred into recipient mice with DSS colitis. This transfer resulted in increased disease activity and inflammatory cytokine production similarly. Taken together, we clearly show that F.nucleatum can promote the progression of UC via proinflammatory M1 macrophage skewing, and targeting F.nucleatum or AKT2 signaling may be a viable means of blocking development of UC.